Miopia tinggi disertai nistagmus Penyebab Low Vision pada Pasien Slow Learner - Cindy Eka Wijaya; Erni Suprihatin; Atti Kartikawati; Suci Haryanti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
On vision examination, it was found that the correction results R / L S -4.00 C -1.50 X 180 (VA ODS = 1/18) there was a sharp increase in vision. This contrast sensitivity to 10% means that the patient's contrast sensitivity decreases. The result of the diagnosis is that the patient is a slow learner with myopia accompanied by nystagmus. Â This research method is with a qualitative approach to the casus study.The management is given the latest prescription glasses and give non-optical tools such as frozen low vision, hats / sunglass, markers, lamps, and others. Advice to parents of patients to be evaluated by an ophthalmologist and routinely check vision at the Low Vision Clinic, the use of glasses is always worn, and gadgets are used not while lying down and reduced the time limit for playing gadgets. Changing a healthy lifestyle such as often seeing green scenery, taking vitamin A, vegetables, fruit, when learning to give bright lighting, healthy activities.